EXPLORING THE LANGUAGE AND REPRESENTATION OF ISLAMIC ETHICS IN THE SONGS OF SAMI YUSUF’S ALBUM SALAAM - Assyifa Putri Azzahra; R. Myrna Nur Sakinah ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
This research explores the use of language and the representation of Islamic ethics in Sami Yusuf's songs contained in the album Salaam. Through a qualitative analytical approach, to provide an in-depth understanding of the use of language used in the lyrics of these songs, as well as the representation of Islamic ethics contained therein, such as love, patience, peace, contentment, and others, delivered through simple and powerful language. An analysis of the lyrics of songs such as “Happiness”, “Salaam”, “Forgotten Promises”, “Hear You Call”, “Smile”, “To Guide You Home”, “Dryer Land”, “All I Need”, “I'm Your Hope”, and “It's A Game” shows that Sami Yusuf uses simple, powerful yet universal language to convey moral and spiritual messages that can be accepted by a global audience. This research shows that the music in the album Salaam serves as a modern medium of da'wah, combining elements of popular culture with Islamic ethical values, thus allowing these messages to reach listeners from different cultural and religious backgrounds.